2016
DOI: 10.1016/j.sjbs.2015.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Embryo apoptosis identification: Oocyte grade or cleavage stage?

Abstract: Apoptosis is a programed cell death that is vital for tissue homeostasis. However, embryo apoptosis had been known to be related to embryo fragmentation which should be avoided in in vitro fertilization (IVF). The purpose of this study was to evaluate the relationship of embryo apoptosis with the grade of immature oocytes and cleavage stage of in vitro produced (IVP) cattle embryos. This study consisted of 345 oocytes collected through ovary slicing. Immature oocytes were graded as A, B and C. This grading was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
5

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 27 publications
(30 reference statements)
1
19
0
5
Order By: Relevance
“…The vast majority of COCs recovered from an isolated ovary are Grade‐3, which are inferior for in vitro maturation, in vitro fertilization, or in vitro culture. Indeed, previous studies (Bakri et al, ; Chauhan et al, ) as well as this study demonstrated the consistently low maturation rate and developmental potential of oocytes from Grade‐3 COCs. One attempt to improve the developmental potential of oocytes from Grade‐3 COCs included co‐culture of these oocytes with additional cumulus cells, but this approach was unsuccessful (Das, Chauhan, Palta, & Tomer, ).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The vast majority of COCs recovered from an isolated ovary are Grade‐3, which are inferior for in vitro maturation, in vitro fertilization, or in vitro culture. Indeed, previous studies (Bakri et al, ; Chauhan et al, ) as well as this study demonstrated the consistently low maturation rate and developmental potential of oocytes from Grade‐3 COCs. One attempt to improve the developmental potential of oocytes from Grade‐3 COCs included co‐culture of these oocytes with additional cumulus cells, but this approach was unsuccessful (Das, Chauhan, Palta, & Tomer, ).…”
Section: Discussionsupporting
confidence: 74%
“…Three grades, in order of diminishing quality, are defined based on these parameters: (i) Grade 1, COCs with an unexpanded cumulus mass (with ≥5 layers of cumulus cells) and with homogeneous ooplasm; (ii) Grade 2, oocytes surrounded by two to four layers of cumulus cells, and with homogenous cytoplasm; or (iii) Grade 3, COCs partially denuded of cumulus cells, and possessing irregular ooplasm (Chauhan, Singla, Palta, Manik, & Madan, ; Wang, Yu, & Xu, ). The average recovery of high‐quality Grade‐1 COCs is about 12 per ovary in cattle, with the majority of the remaining COCs are Grades 2 or 3 (Bakri et al, ; Suss, Wuthrich, & Stranzinger, ). Therefore, protocols to boost the developmental potential of Grade‐3 COCs would provide great benefit to the successful application of assisted reproduction to cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Among the widely used techniques in porcine IVP, in vitro fertilization (IVF), somatic cell nuclear transfer (SCNT) and parthenogenetic activation (PA) are essential for agricultural and biomedical applications (Gil et al., ; Muenthaisong et al., ). Oocyte quality is a determinant in the success of these techniques (El‐Baby et al., ; Gil et al., ; Marteil, Parpaillon, & Kubiak, ; Wu et al., ) because of its effects on the subsequent development competence of the embryo (Bakri et al., ; Goeseels & Panich, ; Krisher, ) and implantation (Danasouri et al., ). In addition, since SCNT and intracytoplasmic sperm injection (ICSI) are technically demanding and time‐consuming procedures, elimination of poor oocytes would increase efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The above suggest that embryos at 2-4 cell can have all the apoptotic machinery due to stimulus however they are not affect mainly due to the immature mitochondria and they might be non-ascertained factors that assist them to overcome some inhibition of apoptosis pathway (Weil et al, 1996;Brad et al, 2007;Bakri et al, 2016).…”
Section: Cell Apoptosis and Bcl-2 Protein Family Genesmentioning
confidence: 96%